2018
DOI: 10.1159/000490725
|View full text |Cite
|
Sign up to set email alerts
|

TDO2 Overexpression Is Associated with Cancer Stem Cells and Poor Prognosis in Esophageal Squamous Cell Carcinoma

Abstract: Objective: Esophageal cancer is one of the deadliest cancers in the world, and the main subtype is esophageal squamous cell carcinoma (ESCC), which comprises 90% of cases. Expression of tryptophan 2,3-dioxygenase (TDO2), an enzyme involved in tryptophan catabolism, has been linked with tumor survival and poor prognosis of brain and breast cancer. However, no studies have investigated the potential role of TDO2 in esophageal cancer. Here we explored the expression and biological significance of TDO2 in ESCC. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 38 publications
(54 reference statements)
5
53
0
Order By: Relevance
“…Obtained data revealed that in rectal cancer samples the kynurenine pathway was characterized by TDO2 overexpression, while IDO1 expression remained practically unchanged (using a 1.5-fold ratio criterion). These data are consistent with others reported in literature, in which TDO2 expression in several human tumor cell lines and tissues has been demonstrated ( 26 , 28 , 40 42 ). Similarly, a rise in the calculated enzymatic activity (KYN/TRP * 1,000) in rectal cancer tissues compared to mucosa was detected (mean activity: 111 and 230 for healthy mucosa and rectal cancer, respectively; p < 0.05, Wilcoxon signed-rank test).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Obtained data revealed that in rectal cancer samples the kynurenine pathway was characterized by TDO2 overexpression, while IDO1 expression remained practically unchanged (using a 1.5-fold ratio criterion). These data are consistent with others reported in literature, in which TDO2 expression in several human tumor cell lines and tissues has been demonstrated ( 26 , 28 , 40 42 ). Similarly, a rise in the calculated enzymatic activity (KYN/TRP * 1,000) in rectal cancer tissues compared to mucosa was detected (mean activity: 111 and 230 for healthy mucosa and rectal cancer, respectively; p < 0.05, Wilcoxon signed-rank test).…”
Section: Resultssupporting
confidence: 94%
“…As observed in other tumors, local TRP depletion in CRC plays an important role in either antitumor immune response suppression or cancer cell proliferation/survival support ( 23 25 ). Beside IDO1, a second enzyme involved in TRP metabolism, tryptophan-2,3-dioxygenase (TDO2) is expressed in a significant proportion of human tumors and is involved in proliferation, migration, invasion, and immunoresistance ( 26 28 ). A valuable way to measure local catabolism is represented by plasma or blood quantification of TRP and its main metabolites, i.e., 5-hydroxy-tryptophan (5-HTP), kynurenine (KYN), and serotonin (5-HT).…”
Section: Introductionmentioning
confidence: 99%
“…26 TDO overexpression is associated with cancer stem cells and poor prognosis in oesophageal squamous cell carcinoma. 27 TDO was significantly upregulated in metastases of leiomyosarcoma patients compared to primary tumours. 28 In addition, high TDO was observed in triple-negative breast cancer (TNBC) compared with ER+ tumours and in stage IV compared with stage III tumours.…”
Section: Discussionmentioning
confidence: 92%
“…All data are from three independent experiments and are presented as the means ± SEM or representative of three independent experiments with similar results (*p < 0.05, **p < 0.01, ***p < 0.001). expressed in human glioma cells and to mediate the Try-Kyn-Ahr pathway, impacting tumor and immune biology regulation; this regulation of the immune response in tumors is exhibited by many human tumors 21,22,41,42 . TDO2 overexpression was associated with cancer stem cells and poor prognosis in esophageal squamous cell carcinoma and TDO2 was significantly upregulated in metastatic leiomyosarcoma tumors compared with the levels in primary tumors.…”
Section: Discussionmentioning
confidence: 99%